Concentrations of levoglucosan, black carbon and ammonium from the RECAP ice core, East Greenland, for the last 5000 years in 20 years bins - Delia Segato; Maria Del Carmen Villoslada Hidalgo; Ross Edwards; Elena Barbaro; Paul T Vallelonga; Helle Astrid Kjær; Marius Simonsen; Bo Møllesøe Vinther; Niccolò Maffezzoli; Roberta Zangrando; Dario Battistel; Carlo Barbante; et al. (PANGAEA, 2021)
This dataset presents the fire proxies levoglucosan, black carbon and ammonium measured in the RECAP ice core, in coastal East Greenland. The datasets cover a period of 5000 years and are averaged in 20 years bins. Levoglucosan has been determined using high performance liquid chromatography/negative ion electrospray ionization – tandem mass spectrometry (HPLC/(-)ESI-MS/MS).9 Black carbon has been measured using a BC analyzer connected to the Continuous Flow Analysis system. Ammonium (NH4+) has been measured by fluorescence within the Continuous Flow Analysis setup.
In: Segato, D et al. (2021): A 5000 year-long record of levoglucosan, black carbon and ammonium from the RECAP ice core, East Greenland [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937438